“Evaluación de fertilizantes foliares en el rendimiento del grano de arroz (Oryza sativa L.), cultivado bajo riego en la zona de Babahoyo” - Vallejo Delgado, Wladimir Sebastian (2018)
VIII. SUMMARY The experimental work was carried out in the lands of the experimental farm "Palmar" belonging to Ability of Agricultural Sciences of the Technical University of Babahoyo. This located in the km 12,5 of the road Babahoyo-Montalvo. It gives birth to the effect seven treatments and three repetitions they were investigated. He/she thought about as objective to evaluate the agronomic behavior of of the rice with the application of nutrition programs to foliate, to determine the most influential program on the production of the cultivation. The crops of the cultivation was carried out with the variety FL-01 in parcels of 16 m2. The used treatments were distributed at random in a design of complete blocks. The evaluation of stockings was made with the test from Tukey to 5 % significance. To measure the effect of the treatments, the variables were measured: height of plants, plants number for m2, grains for panicule, longitude and number of panicule m2, days to flowering, days to crop, number of grains for panicule, weight 1000 seeds, yield for hectare, analysis to foliate and economic analysis. Carried out the variance analyses and evaluation of results, it was determined that the agronomic characteristics of plant height, plants number, panicule/m2, panicule longitude, grains for panicule, days to flowering and days to crop they presented high statistical significance. The biggest production in the cultivation (7351,41 kg/ha) it was in the application of the Program 2 (Quimifol 510 + Enziprom), the witness's plants had the lowest averages in all the studied variables.